The Methanol Extract of Polygonatum odoratum Ameliorates Colitis by Improving Intestinal Short-Chain Fatty Acids and Gas Production to Regulate Microbiota Dysbiosis in Mice - Ye, Xuewei; Pi, Xionge; Zheng, Wenxin; Cen, Yingxin; Ni, Jiahui; Xu, Langyu; Wu, Kefei; Liu, Wei; Li, Lanjuan (Frontiers in Nutrition, 2022)
The potential impacts of methanol extract from Polygonatum odoratum on (YZM) colonic histopathology, gut gas production, short-chain fatty acids (SCFAs), and intestinal microbiota composition were evaluated with dextran sulfate sodium (DSS)-induced colitis mice in this study. These results indicated that YZM increased colon length and ameliorated colonic histopathology in DSS-induced colitis mice. Moreover, YZM administration reversed intestinal microbiota compositions leading to the inhibition of H2S-related bacteria (e.g., Desulfovibrionaceae) and the lower level of H2S and higher contents of SCFA-related bacteria (e.g., Muribaculaceae). Taken together, the effects of methanol extract from Polygonatum odoratum are studied to provide new enlightenment and clues for its application as a functional food and clinical drug. Our study first revealed the relationship between intestinal gas production and key bacteria in ulcerative colitis.